Meningkatkan Keterampilan Berbicara Siswa dengan Media Gambar Seri - Noni Risnawelli (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2017)
Result of initial observation at SDN 18 Batang Anai Kabupaten Padang Pariaman indicated that 1st grade students were afraid and shy to speak in front of class. It was caused the language learning only emphasized on reading and writing skills. Speaking skill was still not being a main focus. This is a classroom action research aimed to improve students’ speaking skill. Data were colected by using test and observation. In cycle I, percentage of students’ speaking skill mean score is 53,3%. In cycle II, percentage of students’ speaking skill mean score is 86%. Hence, learning with media of picture-series can improve students’ speaking skill.